2000
DOI: 10.1111/j.1574-6941.2000.tb00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbofuran degradation mediated by three related plasmid systems

Abstract: Two carbofuran-metabolizing Sphingomonas strains, TA and CD, were isolated from soils with differing histories of exposure to carbofuran. These strains were compared with a previously described strain, Sphingomonas sp. CFO6, with regard to growth rate, formation of metabolites, and plasmid content and structure. Extensive regions of similarity were observed between the three different plasmid systems as evidenced by cross hybridization. In addition, all three systems harbor IS1412, an insertion sequence (IS) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…Several other genes encoding xenobiotic degradation have been found on plasmids in sphingomonads (10,124), and lin genes have been recovered from plasmids in UT26 (113), Spϩ (27), and B90A (86). At least some of the lin gene occurrences outside the sphingomonads are also associated with plasmids (173).…”
Section: Evolutionary Issues and Scope For Improvementmentioning
confidence: 96%
“…Several other genes encoding xenobiotic degradation have been found on plasmids in sphingomonads (10,124), and lin genes have been recovered from plasmids in UT26 (113), Spϩ (27), and B90A (86). At least some of the lin gene occurrences outside the sphingomonads are also associated with plasmids (173).…”
Section: Evolutionary Issues and Scope For Improvementmentioning
confidence: 96%
“…In previous work, it was reported that plasmids are presumably involved in the degradation of naphthalene, biphenyl, toluene, and carbazole by sphingomonads (6,12,47,52). We have obtained evidence that in different sphingomonads the degradative pathways for naphthalenesulfonates, dibenzo-p-dioxin, and dibenzofuran are also encoded on plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in S. aromaticivorans F199 and some other sphingomonads isolated from the same location, the genes encoding the degradative pathways for biphenyl, naphthalene, m-xylene, and p-cresol were detected on large plasmids (29,52). There is also some evidence that the genes for the degradation of carbazole by some other sphingomonads (e.g., Sphingomonas CF06) are also (at least in part) encoded on plasmids (12,47).…”
mentioning
confidence: 99%
“…Also Pinyakong et al (2003a;2003b) observed that, many sphingomonads degrade naphthalene, anthracene, and phenanthalene by common pathways w e r e found in other gram-negative bacteria. In addition, many researchers (Kim et al, 1996;Feng et al, 1997;Romine et al, 1999;Ogram et al, 2000;Basta et al, 2004) found large plasmids in strains of Sphingomonas xenobiotic contributing to the degradation of PAH. (Mrozik et al, 2003).…”
Section: Degradation Study Of Pahmentioning
confidence: 99%